Distinct cortical and collicular mechanisms of inhibition of return revealed with S cone stimuli. - Sumner, P; Nachev, P; Vora, N; Husain, M; Kennard, C (2004)
Visual orienting of attention and gaze are widely considered to be mediated by shared neural pathways, with automatic phenomena such as inhibition of return (IOR)--the bias against returning to recently visited locations--being generated via the direct pathway from retina to superior colliculus (SC). Here, we show that IOR occurs without direct access to the SC, by using a technique that employs stimuli visible only to short-wave-sensitive (S) cones. We found that these stimuli, to which the SC is blind , were quite capable of eliciting IOR, measured by traditional manual responses. Critically, however, we found that S cone stimuli did not cause IOR when saccadic eye movement responses were required. This demonstrates that saccadic IOR is not the same as traditional IOR, providing support for two separate cortical and collicular mechanisms of IOR. These findings represent a clear dissociation between visual orienting of attention and gaze.